Pengaruh Mobile Banking, Internet Banking dan Transformasi Digital terhadap Kinerja Keuangan - Sulpi Tsullatul Awalin; Deden Mulyana; Ati Rosliyati (Jurnal Manajemen Bisnis Era Digital, 2025)
This research aims to determine and analyze the influence of Mobile banking, Internet banking, digital transformation of financial performance in banking companies listed on the IDX for 2019-2023. The sample size was set at 5 banking companies with observation data from 2019 to 2023. The type of data used is secondary data in the form of panel data. The data analysis technique used is multiple linear regression with the Eviews application. The results of this research show that Mobile banking, Internet  Banking and digital transformation simultaneously influences financial performance; Mobile banking partially has a positive and significant effect on financial performance; Internet  Banking partially has a positive but not significant effect on financial performance; Digital transformation partially has a positive but not significant effect on financial performance. It is hoped that companies can implement and improve information technology infrastructure in services digital banking and can be implemented by banking companies to improve company performance.